2019
DOI: 10.1016/j.neurobiolaging.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Prestimulus and poststimulus oscillatory activity predicts successful episodic encoding for both young and older adults

Abstract: Healthy aging is associated with declines in episodic memory performance that are due in part to deficits in encoding. Emerging results from young adult studies suggest that the neural activity during the time preceding stimulus presentation is sensitive to episodic memory performance. It is unknown whether age-related declines in episodic memory are due solely to changes in the recruitment of processes elicited by stimuli during encoding or also in processes recruited in anticipation of these stimuli. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 115 publications
3
22
0
Order By: Relevance
“…Fourth, we investigated whether our data could replicate previous results showing that differences in oscillatory amplitude in the time window around stimulus onset at encoding are predictive of subsequent memory performance (Strunk and Duarte 2019). In order to obtain time-resolved data, oscillatory amplitude values were computed using the Hilbert transform (as specified in the methods section) on a trial by trial basis for theta and alpha frequencies.…”
Section: Reality Checks and Alternative Phase-opposition Analysismentioning
confidence: 79%
“…Fourth, we investigated whether our data could replicate previous results showing that differences in oscillatory amplitude in the time window around stimulus onset at encoding are predictive of subsequent memory performance (Strunk and Duarte 2019). In order to obtain time-resolved data, oscillatory amplitude values were computed using the Hilbert transform (as specified in the methods section) on a trial by trial basis for theta and alpha frequencies.…”
Section: Reality Checks and Alternative Phase-opposition Analysismentioning
confidence: 79%
“…This finding was interpreted as evidence that the older adults did not engage in effective preparation for the upcoming study event, an account consistent with a broader body of research suggesting that older adults do not spontaneously engage 'proactive' control. By contrast, an EEG study by Strunk & Duarte (2019) reported age-invariant effects in time-frequency measures of pre-stimulus neural activity elicited by pre-stimulus cues that signaled the modality of the upcoming study item. Contrary to the conclusions of Koen et al (2018), these authors proposed that older and young adults were equally capable of engaging pre-stimulus anticipatory processes that facilitate episodic encoding.…”
mentioning
confidence: 88%
“…Although it has been reported that older adults demonstrate reduced pre-stimulus SMEs(Koen et al, 2018), findings of age-invariant pre-stimulus SMEs are not unprecedented. Notably,Strunk & Duarte (2019) reported age-invariant pre-stimulus SMEs in oscillatory neural activity elicited by informative cues that signaled the modality of the upcoming study item. The authors interpreted these findings as evidence for intact pre-stimulus preparatory processes in their older adults.The significance of the present age-invariant findings depends heavily on the interpretation given to the pre-stimulus SMEs that were identified (see above).…”
mentioning
confidence: 99%
“…In addition, a substantial body of research has shown that successful encoding depends also on the neural activity occurring a second or so before presentation of a to-be-remembered item (Addante, de Chastelaine, & Rugg, 2015;. Theta oscillations (4-8 Hz) have been shown to play an important part in memory, whereby prestimulus theta activity was found to be associated with more effective encoding in younger and also older adults (Addante, Watrous, Yonelinas, Ekstrom, & Ranganath, 2011;Strunk & Duarte, 2019), indicating that this prestimulus theta activity is relatively spared with ageing.…”
Section: Introductionmentioning
confidence: 99%